PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 010 SIMPANG PELITA KECAMATAN KUBU KABUPATEN ROKAN HILIR - Yunita, Sri; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study starts from the low IPS student learning outcomes, with anaverage value of 64.6 class. While the value of minimum completeness criteria(KKM) IPS 65. This research is a classroom action research (CAR). Conductedaiming to improve learning outcomes IPS 010 fifth grade students of SDN PelitaSimpang Kubu district of Rokan Hilir. Formulation of the problem: Is theapplication of guided inquiry learning model to improve learning outcomes IPS010 fifth grade students of SDN Pelita Simpang Kubu district of Rokan Hilir. Asfor the improvement of learning outcomes that occur before and after a cycle ofPTK held one in an increase of 64.6 with less category, while after the ClassAction Research in the first cycle of 72 with enough categories and cycleIIsebesar 83.75 with either category. Overall, therefore, an increase in studentlearning outcomes of basic scores kesiklus one of a score of 7.4 while the twokesiklus base increased by 11.75. While the activity of the teachers who have anaverage amount in the first cycle with an average of 66.66% with enoughcategories, while the second cycle is the average of 85.41% with very goodcategory. Being the student activity at the second meeting of the first cycle with anaverage of 60.41% while the two cycles increased to 79.16%. These results provethat the application of learning models to Make a match can improve learningoutcomes IPS 010 fifth grade students of SDN Pelita Simpang Kubu district ofRokan Hilir.KeywordsCooperative type make a match, Social Science Learning Outcomes2PENERAPAN